Allocation of virtual infrastructures on multiple iaas providers with survivability and reliability requirements - Raugust A.S.* (2018)
© 2018 IEEE.The cloud computing paradigm consolidated the on-demand provisioning of virtual resources. However, the diversity of services, prices, data centers, and geographical footprints, have turned the clouds into a complex and heterogeneous environment. There are several IaaS providers differentiated by the provisioning costs and availability figures. Due to management complexity, the survivability and reliability aspects are often disregarded by tenants, eventually resulting in heavy losses due to unavailability of services that are hosted on Virtual Infrastructures (VIs). We present an alternative to improve VIs survivability and reliability, which considers the use of replicas and the spreading of virtual resources atop providers, regions, and zones. Replicas are used to achieve a user-defined reliability level while the controlled spreading of VI components decrease the probability of full outages. In addition, our proposal performs a cost-effective allocation. We formulate the VI allocation with survivability and reliability requirements as a Mixed Integer Program (MIP). Following, binary constraints are relaxed to obtain a Linear Program (LP). The LP solution is given as input for the simulated annealing technique, composing the Reliable and Survivable Virtual Infrastructure Allocation (RS-VIA) mechanism. Simulation results with different reliability requests indicate an increasing in survivability without inflating costs.